Pengaruh Pengaplikasian Beberapa Konsentrasi Plant Growth Promoting Rhizobacteria Akar Bambu terhadap Pertumbuhan dan Produksi Kacang Tunggak - Galushasti, Andarula; Khusna, Nisa Wardatul; Soelaksini, Liliek Dwi; Jumiatun (Program Studi Agroteknologi INSTIPER, 2025)
Cowpea (Vigna unguiculata L.) is one of the food crops with relatively high protein content, but its production remains relatively low. The applied cultivation technology is still not optimal, resulting in no significant increase in cowpea production. This study aims to determine the effect of applying various concentrations of Plant Growth Promoting Rhizobacteria (PGPR) on the growth and production of cowpea. The research was conducted at the Jember State Polytechnic field from July 2024 to October 2024. The study used a Non-Factorial Randomized Block Design (RBD) with 6 treatments and 4 replications. The treatments consisted of PGPR concentrations of 0 ml/L, 18 ml/L, 29 ml/L, 40 ml/L, and 51 ml/L. The observed variables included plant height, stem diameter, number of sample pods, fresh weight of sample pods, fresh weight of pods per plot, dry weight of sample pods, dry weight of pods per plot, dry seed weight per plot, and weight of 100 seeds per plot. The results showed that the PGPR treatment at a concentration of 51 ml/L significantly affected plant height, dry seed weight of samples, and weight of 100 seeds per plot. This is likely due to the role of PGPR as a biofertilizer and biostimulant. However, there were no significant differences in stem diameter, number of sample pods, fresh weight of sample pods, fresh weight of pods per plot, dry weight of sample pods, dry weight of pods per plot, and dry seed weight per plot.